Empowering customer awareness through social network: a case study of Sukimi Group / Sulaiman Ismail - Ismail, Sulaiman (UNIVERSITI TEKNOLOGI MARA KELANTAN KOTA BHARU CITY CAMPUS, 2012)
This study was conducted at Sukimi Group. This research was targeted on the social network users either customer to Sukimi Group or not. The study is about on “Empowering Customer Awareness through Social Network: A Case Study of Sukimi Group”. The objective of this research is to identify the factors will influence customers’ awareness toward Sukimi’s products, to evaluate the relationship between independent variables which is customer attractions, customer engagements and customer retentions with the customer awareness as the dependent variables and to identify the most and the least factors that contribute to the customer’s awareness via social networks whether customer attractions, customer retentions and customers engagements. The theoretical framework for this study consists of dependent variable and independent variable. Dependent variable for this research is customer satisfaction and independent variables are the factors that influence customer awareness. Researcher had identified three independent variables such as customer attraction, customer engagement and customer retention. Data were collected through questionnaire that consist 5 sections. For this research, the sample size will be 100 respondents. From the findings, the researcher can conclude all independent variable (IV) be acceptable as show as the table at the Chapter 4 that have significant relationship with dependant variables (DV). All IV have moderate correlation and substantial relationship proved by Pearson Correlation. Based on findings also, the most IV is customer attractions. The respondents agreed the customer attractions are suitable to be use in increase customer awareness via social network. After going through the findings and analysis process, the researcher provided recommendation and suggestion in empowering customer awareness. All the recommendation will be give benefit to the organization to take action in order to increase the customer awareness toward the company brand name.